Agronomic, economic and environmental analyses of dual-purpose wheat cultivars for bioenergy - Townsend, Toby J. (2014)
Concerns about climate change and energy supply security have led to a focus on using biofuels to replace oil-based fuels in the transport sector. Second generation biofuels (SGBs), which are produced from lignocellulosic material such as wheat straw, are currently being developed.